Characteristics Of Education And Intellectual Education Of Primary Class Students (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The purpose of this article is to determine the content of the concepts of "self-organization", "self-learning", and to determine the features of independent learning in the process of mental development of primary school students based on a synergistic approach.